Effect of digestate / biogas slurry on wheat under rice – wheat cropping system - Pandey, B. P.; Khatri, N.; Yadav, M.; Pant, K. R.; Poudel, R. P.; Khan, A. H. (Journal of Agriculture and Forestry University, 2020)
Soil fertility in several parts of Nepal is declining mainly due to continuous cultivation and without replenishing soil nutrient removal by crops with quality fertilizers in required quantity. Nepal does not produce chemical fertilizers and most farmers cannot afford to buy the imported fertilizer. Under these circumstances, emphasizing locally available low cost organic manure may become an important option. This research compares the effect of different stages [5 days (fresh), 90 days (3 months) and 180 days (6 months)], and dose (0, 5, 10 and 15 t ha-1) of digestate/biogas slurry on wheat yield. Field experiments were conducted during winter seasons of 2016 – 2017 (first year) and 2017 - 2018 (second year) in a silt loam soil to identify suitable stage and appropriate dose of digestate regarding yield maximization of wheat. The experiment was done by using 2 factors Randomized Complete Block Design (RCBD), each treatment with three replications. Grain yield was significantly higher (2.2 t ha-1) due to application of biogas slurry of 5 days stage than the stage of 90 days (2.1 t ha-1) in 2016 - 2017, 2017 – 2018 and in pooled analysis. Grain yield increased significantly up to the dose of 10 t ha-1 as compared to that of no use (check), and became saturated, in 2016 – 2017, 2017 – 2018, and also in pooled analysis. Hence, the use of biogas slurry of the stage of 5 days with the dose of 10 t ha-1 resulted higher grain yield of wheat (cv. Vijay), is edaphically and economically viable option for wheat production.